A high temperature resistant coating film, preparation method and electrochemical device thereof
By applying a high-temperature coating film containing ultraviolet initiator and polymer emulsion on the lithium-ion battery separator, the problem of insufficient safety of the existing separator under high temperature conditions is solved, and a higher film rupture temperature and closed-cell temperature are achieved, which significantly improves the high-temperature safety performance of the battery.
Patent Information
- Application Number
- CN202410613670.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2021-07-13
- Publication Date
- 2025-04-04
AI Technical Summary
The existing lithium-ion battery separators are insufficient in high temperature conditions, making it difficult to effectively increase the membrane rupture temperature and reduce the closed-cell temperature, resulting in safety risks such as short circuits and liquid leakage in high-temperature environments.
A high-temperature resistant coating film is adopted, and the coating slurry contains components such as ultraviolet initiator, ultraviolet crosslinking, polymer emulsion, etc., and a coating film with high closed-cell temperature and rupture temperature is formed by ultraviolet radiation, thereby enhancing the high-temperature dimensional stability and safety of the battery.
The safety interval between the rupture temperature of the diaphragm and the closed-cell temperature is significantly improved, the safety performance of the battery under high temperature conditions is enhanced, the risks of short circuits and liquid leakage are reduced, and the overall safety factor of the battery is improved.
Smart Images

Figure BDA0004844415470000221 
Figure BDA0004844415470000241 
Figure BDA0004844415470000261
Abstract
Description
[0001] This invention is a divisional application. The filing date of the original application is July 13, 2021. The application number is 202110787905.8. The name of the invention is: A high temperature resistant coating film, preparation method and electrochemical device thereof. Technical Field
[0002] The present invention relates to the field of battery separators, and in particular to a high temperature resistant coating film, a preparation method and an electrochemical device thereof. Background Art
[0003] The diaphragm is an important component of lithium-ion batteries. It has two main functions. The first is electronic insulation, which ensures electronic insulation between the positive and negative electrodes of lithium-ion batteries to prevent short circuits. The second function is to conduct ions. The electrolyte can penetrate into the porous structure of the diaphragm, allowing ions to pass through the diaphragm and achieve ion conduction.
[0004] In the structure of lithium batteries, the diaphragm is one of the key internal components. The performance of the diaphragm determines the interface structure and internal resistance of the battery, and directly affects the battery capacity, cycle and safety performance. It can be said that a diaphragm with excellent performance plays a decisive role in improving the comprehensive performance of the battery. With the continuous development of lithium batteries, the performance requirements of the diaphragm are getting higher and higher. In terms of high energy density, the base film and coating are required to be thinner and lighter, and the sticky coating is used to improve the volume energy density of the battery cell; in terms of long life, it is necessary to enhance the liquid retention and wettability of the diaphragm, improve the lithium ion conductivity, increase the battery hardness, and inhibit the battery cycle deformation; in terms of high safety, it is necessary to use an ultra-high strength base film, increase the base film rupture temperature, reduce the closed cell temperature, inhibit the formation of dendrites, and reduce the risk of battery leakage and spontaneous combustion.
[0005] The temperature range from the closed-cell temperature to the rupture temperature of the battery diaphragm is the safe range that the battery can withstand high temperatures. The larger the temperature range, the higher the safety factor when the battery is affected by high temperatures. Therefore, lowering the closed-cell temperature and increasing the rupture temperature are crucial to improving the overall safety performance of the battery. In the prior art, high-safety diaphragms are generally achieved by technical means such as PE / PP multi-layer composite diaphragms and high-heat-resistant ceramics. The method of preparing composite diaphragms by PP / PE multi-layer co-extrusion is difficult due to the large difference in PP / PE stretching processing temperature; while the high-heat-resistant ceramic coating method can form a layer of ceramic coating on the surface of the diaphragm, which can effectively improve the high-temperature dimensional stability of the diaphragm, but the diaphragm rupture temperature depends on the coated base film, and the ceramic coating has little effect on the rupture temperature of the entire diaphragm. Although ceramic coating can improve the overall high-temperature dimensional stability, when the temperature is too high, even if the ceramic coating can maintain the membrane structure, the base film layer will rupture, which will cause the closed-cell effect to disappear.
[0006] Patents CN201310111465.X and CN201610786396.6 provide methods for manufacturing high temperature resistant diaphragms, but both are improvements of low closed-cell temperature coatings on high temperature resistant non-woven fabric base membranes. Summary of the invention
[0007] In view of this, the present invention hopes to provide a high temperature resistant coating film and a preparation method thereof to solve the above technical problems.
[0008] To achieve the above object, the technical solution of the present invention is achieved as follows:
[0009] The present invention aims to provide a high temperature resistant coating film, the safety interval of which is 35 to 91°C. Preferably, the safety interval is 35 to 75°C. Preferably, the safety interval is 50 to 91°C.
[0010] Furthermore, the thickness of the high temperature resistant coating film is 9 to 18 μm. Preferably, the thickness is 9 to 13 μm.
[0011] Further, the air permeability of the high temperature resistant coating film is 144-230s / 100ml. Preferably, the air permeability is 152-230s / 100ml. Preferably, the air permeability is 176-230s / 100ml. Preferably, the air permeability is 176-206s / 100ml.
[0012] Furthermore, the needle puncture strength of the high temperature resistant coating film is 472 to 616 gf. Preferably, the needle puncture strength is 473 to 509 gf.
[0013] Further, the closed-cell temperature of the high-temperature resistant coating film is 95 to 143° C. Preferably, the closed-cell temperature is 95 to 141° C. Preferably, the closed-cell temperature is 95 to 121° C. Preferably, the closed-cell temperature is 140 to 142° C.
[0014] Furthermore, the film breaking temperature of the high temperature resistant coating film is 172-216° C. Preferably, the film breaking temperature is 176-216° C. Preferably, the film breaking temperature is 172-187° C.
[0015] Further, the high temperature resistant coating film includes a substrate and a coating slurry on at least one surface of the substrate; the coating slurry includes the following components in mass percentage: 0.01-5% of ultraviolet initiator, 0.01-5% of ultraviolet crosslinker, 0-50% of deionized water, and 5-70% of organic solvent. Preferably, the coating slurry includes the following components in mass percentage: 0.01-2% of ultraviolet initiator, 0.7-3.5% of ultraviolet crosslinker, 0-50% of deionized water, and 8-58% of organic solvent. Preferably, the coating slurry includes the following components in mass percentage: 0.1-2% of ultraviolet initiator, 0.7-3.5% of ultraviolet crosslinker, 0-50% of deionized water, and 8-58% of organic solvent.
[0016] Further, the high temperature resistant coating film includes a substrate and a coating slurry on at least one surface of the substrate; the coating slurry includes the following components in mass percentage: 0.01-5% of ultraviolet initiator, 0.01-5% of ultraviolet crosslinker, 0-90% of polymer emulsion, and 5-70% of organic solvent. Preferably, the coating slurry includes the following components in mass percentage: 0.01-2% of ultraviolet initiator, 0.7-3.5% of ultraviolet crosslinker, 0-83% of polymer emulsion, and 8-58% of organic solvent. Preferably, the coating slurry includes the following components in mass percentage: 0.1-2% of ultraviolet initiator, 0.7-3.5% of ultraviolet crosslinker, 0-83% of polymer emulsion, and 8-58% of organic solvent. Preferably, the coating slurry comprises the following components in percentage by mass: 0.1-0.5% of ultraviolet light initiator, 0.7-0.9% of ultraviolet light crosslinking agent, 46-83% of polymer emulsion, and 8-29% of organic solvent.
[0017] Further, the high temperature resistant coating film comprises a substrate and a coating slurry on at least one surface of the substrate; the coating slurry comprises the following components in mass percentage: 0.01-5% of ultraviolet initiator, 0.01-5% of ultraviolet crosslinker, 0-50% of deionized water, 0-90% of polymer emulsion, 0-10% of binder, 0-5% of dispersant, and 5-70% of organic solvent. Preferably, the coating slurry comprises the following components in mass percentage: 0.01-2% of ultraviolet initiator, 0.7-3.5% of ultraviolet crosslinker, 0-50% of deionized water, 0-83% of polymer emulsion, 0-4.5% of binder, 0-1.5% of dispersant, and 8-58% of organic solvent. Preferably, the coating slurry comprises the following components in mass percentage: 0.1-2% UV initiator, 0.7-3.5% UV crosslinker, 0-50% deionized water, 0-83% polymer emulsion, 0-4.5% binder, 0-1.5% dispersant, and 8-58% organic solvent. Preferably, the coating slurry comprises the following components in mass percentage: 0.1-0.5% UV initiator, 0.7-0.9% UV crosslinker, 0-19% deionized water, 46-83% polymer emulsion, 0-4.1% binder, 0-1.2% dispersant, and 8-29% organic solvent. Preferably, the coating slurry comprises the following components in percentage by mass: 0.3-0.5% UV initiator, 0.7-0.9% UV crosslinker, 4-19% deionized water, 47-81% polymer emulsion, 3.5-4.1% binder, 0.9-1.2% dispersant, and 8-29% organic solvent, and the polymer emulsion is a polyolefin emulsion.
[0018] Preferably, the substrate is a polyolefin membrane or a polyolefin membrane containing a ceramic coating.
[0019] Furthermore, the polyolefin in the polyolefin membrane or the polyolefin membrane containing a ceramic coating is one or a mixture of two or more of the following crystalline polymers: polyethylene, polypropylene, poly-1-butene, poly-4-methyl-1-pentene, poly-1-hexene, poly-1-octene, polymethyl methacrylate.
[0020] Preferably, the organic solvent is an organic solvent that is miscible with water in any proportion. Further, the organic solvent is anhydrous ethanol.
[0021] Preferably, the ultraviolet light initiator is a cationic light initiator or a free radical light initiator. Further, the ultraviolet light initiator is 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone or benzophenone.
[0022] Preferably, the ultraviolet crosslinking agent is an allyl crosslinking aid.
[0023] Furthermore, the allyl cross-linking aid is selected from one or a mixture of two or more of the following: trimethylolpropane trimethacrylate, trimethylolpropane triacrylate, tripropylene cyanurate, and triallyl isocyanurate.
[0024] Preferably, the polymer emulsion is a polyolefin emulsion, an acrylate emulsion and an emulsion of its derivatives.
[0025] Furthermore, the solid content of the polymer emulsion is between 10% and 70%, wherein the size of the solid particles is 0.5 μm≤D(50)≤5 μm.
[0026] Furthermore, the size of the solid particles is 0.5 μm ≤ D(50) ≤ 2.5 μm. Furthermore, the size of the solid particles is 0.6 μm ≤ D(50) ≤ 1.5 μm. Furthermore, the size of the solid particles is 1 μm ≤ D(50) ≤ 1.5 μm.
[0027] Furthermore, when the polymer emulsion is a polyolefin emulsion, the melting point of the solid particles is 60 to 160°C.
[0028] Furthermore, the melting point of the solid particles is 80-135°C. Furthermore, the melting point of the solid particles is 80-120°C. Furthermore, the melting point of the solid particles is 110-120°C. Furthermore, the melting point of the solid particles is 80-90°C.
[0029] Furthermore, when the polymer emulsion is a polyolefin emulsion, the solid content of the polymer emulsion is 42%, wherein the size of the solid particles is D(50)=1.5 μm, and the melting point of the solid particles is 110-120°C.
[0030] Furthermore, when the polymer emulsion is a polyolefin emulsion, the solid content of the polymer emulsion is 35%, wherein the size of the solid particles is D(50)=1.0 μm, and the melting point of the solid particles is 80-90°C.
[0031] Furthermore, when the polymer emulsion is a polyolefin emulsion, the solid content of the polymer emulsion is 65%, wherein the size of the solid particles is D(50)=1.2 μm, and the melting point of the solid particles is 110-120°C.
[0032] Preferably, the binder is selected from one or more of polyacrylate and its derivatives, polyvinyl alcohol and its derivatives, and polyvinyl acetate.
[0033] Preferably, the dispersant is an anionic surfactant or a cationic surfactant. Further, the dispersant is dodecyl dimethyl betaine or sodium linear alkyl benzene sulfonate.
[0034] Furthermore, the ultraviolet light initiator is benzophenone, the ultraviolet light cross-linking agent is triallyl isocyanurate, and the organic solvent is anhydrous ethanol.
[0035] Furthermore, the ultraviolet light initiator is 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, the ultraviolet light crosslinking agent is triallyl isocyanurate, and the organic solvent is anhydrous ethanol.
[0036] Further, the ultraviolet initiator is benzophenone, the ultraviolet crosslinker is trimethylolpropane trimethacrylate, the polymer emulsion is an acrylate and its derivative emulsion, and the organic solvent is anhydrous ethanol. Preferably, the ultraviolet initiator is benzophenone, the ultraviolet crosslinker is trimethylolpropane trimethacrylate, the polymer emulsion is an acrylate and its derivative emulsion, the organic solvent is anhydrous ethanol, and the solid content of the acrylate copolymer polymer emulsion in the acrylate and its derivative emulsion is 33%, and the particle size D(50) of the solid particles is 0.6μm.
[0037] Further, the ultraviolet initiator is 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, the ultraviolet crosslinker is trimethylolpropane trimethacrylate, and the dispersant is dodecyl dimethyl betaine. Preferably, the ultraviolet initiator is 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, the ultraviolet crosslinker is trimethylolpropane trimethacrylate, the dispersant is dodecyl dimethyl betaine, the binder is polyacrylate, the polymer emulsion is polyolefin emulsion, and the organic solvent is anhydrous ethanol. Preferably, the ultraviolet initiator is 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, the ultraviolet crosslinker is trimethylolpropane trimethacrylate, the dispersant is dodecyl dimethyl betaine, the binder is polyacrylate, the polymer emulsion is a polyolefin emulsion, the organic solvent is anhydrous ethanol, and the solid polyolefin particles in the polyolefin emulsion have a melting point between 110 and 120° C., the particle size D(50) of the polyolefin particles is 1.5 μm, and the solid content of the solid polyolefin particles in the polyolefin emulsion is 42%.
[0038] Further, the ultraviolet initiator is benzophenone, the ultraviolet crosslinker is trimethylolpropane trimethacrylate, and the dispersant is linear sodium alkylbenzene sulfonate. Preferably, the ultraviolet initiator is benzophenone, the ultraviolet crosslinker is trimethylolpropane trimethacrylate, the dispersant is linear sodium alkylbenzene sulfonate, the binder is polyacrylate, the polymer emulsion is a polyolefin emulsion, and the organic solvent is anhydrous ethanol. Preferably, the ultraviolet initiator is benzophenone, the ultraviolet crosslinker is trimethylolpropane trimethacrylate, the dispersant is linear sodium alkylbenzene sulfonate, the binder is polyacrylate, the polymer emulsion is a polyolefin emulsion, the organic solvent is anhydrous ethanol, and the solid polyolefin particles in the polyolefin emulsion have a melting point between 80 and 90°C, the particle size D(50) of the polyolefin particles is 1.0 μm, and the solid content of the solid polyolefin particles in the polyolefin emulsion is 35%.
[0039] Further, the UV initiator is benzophenone, the UV crosslinker is triallyl isocyanurate, and the dispersant is linear sodium alkylbenzene sulfonate. Preferably, the UV initiator is benzophenone, the UV crosslinker is trimethylolpropane trimethacrylate, the dispersant is linear sodium alkylbenzene sulfonate, the binder is polyacrylate, the polymer emulsion is polyolefin emulsion, and the organic solvent is anhydrous ethanol. Preferably, the ultraviolet initiator is benzophenone, the ultraviolet crosslinker is trimethylolpropane trimethacrylate, the dispersant is linear alkylbenzene sodium sulfonate, the binder is polyacrylate, the polymer emulsion is a polyolefin emulsion, the organic solvent is anhydrous ethanol, and the solid polyolefin particles in the polyolefin emulsion have a melting point between 110 and 120°C, the particle size D(50) of the polyolefin particles is 1.2 μm, and the solid content of the solid polyolefin particles in the polyolefin emulsion is 65%.
[0040] The object of the present invention is to provide a high temperature resistant coating film, comprising a substrate and a coating slurry on at least one surface of the substrate; the coating slurry comprises the following components in percentage by mass: 0.01-5% of ultraviolet initiator, 0.01-5% of ultraviolet crosslinker, 0-50% of deionized water, 0-90% of polymer emulsion, 0-10% of binder, 0-5% of dispersant, and 5-70% of organic solvent.
[0041] Furthermore, the coating slurry comprises the following components in percentage by mass: 0.01-2% of ultraviolet initiator, 0.7-3.5% of ultraviolet crosslinker, 0-50% of deionized water, 0-83% of polymer emulsion, 0-4.5% of binder, 0-1.5% of dispersant, and 8-58% of organic solvent.
[0042] Furthermore, the substrate is a polyolefin membrane or a polyolefin membrane containing a ceramic coating.
[0043] Furthermore, the polyolefin in the polyolefin membrane or the polyolefin membrane containing a ceramic coating is one or a mixture of two or more of the following crystalline polymers: polyethylene, polypropylene, poly-1-butene, poly-4-methyl-1-pentene, poly-1-hexene, poly-1-octene, polymethyl methacrylate.
[0044] Furthermore, the organic solvent is an organic solvent that is miscible with water in any proportion.
[0045] Furthermore, the ultraviolet light initiator is a cationic light initiator or a free radical light initiator.
[0046] Furthermore, the ultraviolet crosslinking agent is an allyl auxiliary crosslinking agent.
[0047] Furthermore, the allyl cross-linking aid is selected from one or a mixture of two or more of the following: trimethylolpropane trimethacrylate, trimethylolpropane triacrylate, triallyl cyanurate and triallyl isocyanurate.
[0048] Furthermore, the polymer emulsion is a polyolefin emulsion, an acrylate emulsion and an emulsion of its derivatives.
[0049] Furthermore, the solid content of the polymer emulsion is between 10% and 70%, wherein the size of the solid particles is 0.5 μm≤D(50)≤5 μm.
[0050] Preferably, the size of the solid particles is 0.5 μm≤D(50)≤2.5 μm.
[0051] More preferably, the size of the solid particles is 0.6 μm≤D(50)≤1.5 μm.
[0052] More preferably, the size of the solid particles is 1 μm≤D(50)≤1.5 μm.
[0053] Furthermore, when the polymer emulsion is a polyolefin emulsion, the melting point of the solid particles is 60 to 160°C.
[0054] Preferably, the melting point of the solid particles is 80-135°C, more preferably 80-120°C, more preferably 110-120°C, and even more preferably 80-90°C.
[0055] Furthermore, the binder is selected from one or more of polyacrylate and its derivatives, polyvinyl alcohol and its derivatives, and polyvinyl acetate.
[0056] Furthermore, the dispersant is an anionic surfactant or a cationic surfactant.
[0057] Further, the high temperature resistant coating film has a thickness of 9 to 18 μm, an air permeability of 144 to 230 s / 100 ml, a puncture strength of 472 to 616 gf, a closed cell temperature of 95 to 143 ° C, a film breaking temperature of 172 to 216 ° C, and a safety interval of 35 to 91 ° C. Preferably, the thickness is 9 to 18 μm, the air permeability is 176 to 230 s / 100 ml, the puncture strength is 473 to 509 gf, the closed cell temperature is 95 to 141 ° C, the film breaking temperature is 172 to 216 ° C, and the safety interval is 35 to 91 ° C.
[0058] It can be further preferably set to a thickness of 9 to 13 μm, an air permeability of 176 to 206 s / 100 ml, a puncture strength of 473 to 509 gf, a closed-cell temperature of 140 to 142°C, a film-breaking temperature of 176 to 216°C, and a safety interval of 35 to 75°C.
[0059] It can be further preferably set to a thickness of 9 to 18 μm, an air permeability of 152 to 230 s / 100 ml, a closed-cell temperature of 95 to 121° C., a film-breaking temperature of 172 to 187° C., and a safety interval of 50 to 91° C.
[0060] The present invention also aims to provide an electrochemical device, comprising a positive electrode, a negative electrode, an electrolyte and a coating film; the coating film comprises a polyolefin separator or a polyolefin separator containing a ceramic coating as a substrate and a coating slurry adhered to at least one surface of the substrate, the coating slurry comprising: an organic solvent, an ultraviolet light initiator, an ultraviolet light cross-linking agent, water, a polymer emulsion, a binder, and a dispersant.
[0061] The present invention also aims to provide a method for preparing a high temperature resistant coating film, comprising the following steps:
[0062] 1) dissolving an ultraviolet light initiator, an ultraviolet light crosslinking agent, a polymer emulsion, a binder, and a dispersant in a solvent to form a coating slurry, wherein the weight percentage of the slurry is 0.01-5% of the ultraviolet light initiator, 0.01-5% of the ultraviolet light crosslinking agent, 0-50% of deionized water, 0-90% of the polymer emulsion, 0-10% of the binder, 0-5% of the dispersant, and 5-70% of the organic solvent;
[0063] 2) The coating slurry is uniformly coated on one or both sides of the substrate, and the high temperature resistant coating film is formed after ultraviolet irradiation.
[0064] Furthermore, the components of the slurry in step 1) are preferably 0.1-2% UV initiator, 0.7-3.5% UV crosslinker, 0-50% deionized water, 0-83% polymer emulsion, 0-4.5% binder, 0-1.5% dispersant, and 8-58% organic solvent.
[0065] Furthermore, the organic solvent is miscible with deionized water in any proportion.
[0066] Furthermore, the organic solvent is selected from one or a mixture of two or more of ethanol, acetone, isopropanol, dimethylformamide, N,N-dimethylformamide, and dimethyl sulfoxide.
[0067] Furthermore, the polymer emulsion is a polyolefin emulsion, an acrylate emulsion and an emulsion of its derivatives; the solid content of the polymer emulsion is 10% to 70%, wherein the size of the solid particles is 0.5 μm≤D(50)≤5 μm.
[0068] Furthermore, when the polymer emulsion is a polyolefin emulsion, the melting point of the solid particles is 60 to 160°C.
[0069] The beneficial effects of the present invention are as follows:
[0070] First, the present invention provides a high temperature resistant coating film, which has a larger temperature difference (safety interval) between the closed-cell temperature and the film-breaking temperature than the prior art. Specifically, when the diaphragm temperature is at the closed-cell temperature, the pores will collapse and block the current, but the thermal inertia will still cause the diaphragm temperature to continue to rise. When the diaphragm temperature reaches the film-breaking temperature, the diaphragm melt will rupture, causing a short circuit in the battery. Therefore, the high temperature resistant coating film based on the present invention has a relatively high safety interval, which can provide the safety of battery use. Secondly, the high temperature resistant coating film of the present invention can be coated on at least one side of the substrate with a specially formulated coating slurry. When the substrate has the same thickness, the physical and chemical properties of the high temperature resistant coating film of the present invention, such as air permeability, are equivalent, and there is a comparable or very low closed-cell temperature and a very high film-breaking temperature. The high temperature resistant coating film of the present invention has excellent thermal properties and a large safety interval. When used in a battery, it can prevent the battery from overheating and short-circuiting, effectively ensure the safety of the battery machinery and high temperature abuse scenarios, and the overall safety factor of the battery has been greatly improved. DETAILED DESCRIPTION
[0071] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0072] A specific embodiment of the present invention provides a method for preparing a high temperature resistant coating film, comprising the following steps:
[0073] 1) dissolving an ultraviolet light initiator, an ultraviolet light crosslinking agent, a polymer emulsion, a binder, and a dispersant in a solvent to form a coating slurry, wherein the weight percentage of the slurry is 0.01-5% of the ultraviolet light initiator, 0.01-5% of the ultraviolet light crosslinking agent, 0-50% of deionized water, 0-90% of the polymer emulsion, 0-10% of the binder, 0-5% of the dispersant, and 5-70% of the organic solvent;
[0074] 2) The coating slurry is uniformly coated on one or both sides of the substrate, and the high temperature resistant coating film is formed after ultraviolet irradiation.
[0075] Furthermore, the ultraviolet light initiator is a cationic light initiator or a free radical light initiator.
[0076] The ultraviolet light initiator is preferably selected from the group consisting of benzoin, benzoin dimethyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin butyl ether, diphenyl acetone, α, α-dimethoxy-α-phenylacetophenone, α, α-diethoxyacetophenone, α-hydroxyalkyl phenone, α-aminoalkyl phenone, aromatic acyl phosphine oxide, bisbenzoylphenyl phosphine oxide, benzophenone, 2,4-dihydroxybenzophenone, 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, Michler's ketone, thiopropoxythioxanthone, isopropylthioxanthone, diaryl iodonium salts, triaryl iodonium salts, alkyl iodonium salts, and cumene ferrocenium hexafluorophosphate.
[0077] Furthermore, the ultraviolet crosslinking agent is an allyl auxiliary crosslinking agent.
[0078] The allyl cross-linking auxiliary agent is preferably selected from one or a mixture of two or more of the following: trimethylolpropane trimethacrylate, trimethylolpropane triacrylate, triallyl cyanurate and triallyl isocyanurate.
[0079] Furthermore, the polymer emulsion is a polyolefin emulsion or an acrylate emulsion (for example, its related derivatives, preferably one or more of the following substances with a glass transition temperature Tg>90°C: methyl methacrylate, acrylic acid, methacrylic acid, acrylonitrile, acrylamide, methacrylate copolymers such as isobornyl methacrylate).
[0080] The function of the polymer emulsion is to introduce polymer microparticles having a melting point or glass transition temperature lower than the melting point of the polyolefin-based film and coat them on the surface of the film, but the polymer microparticles need to be prepared into an emulsion for use.
[0081] Furthermore, the solid content of the polymer emulsion is between 10% and 70%, further preferably between 33% and 42%, further preferably between 35% and 42%, wherein the size of the solid particles is 0.5 μm ≤ D(50) ≤ 5 μm, further preferably between 0.5 μm ≤ D(50) ≤ 2.5 μm, further preferably between 0.6 μm ≤ D(50) ≤ 1.5 μm, and further preferably between 1 μm ≤ D(50) ≤ 1.5 μm.
[0082] Here, when the solid content is greater than 70%, the viscosity is too high and is not conducive to coating, and when the solid content is less than 10%, a uniform coating cannot be formed.
[0083] Here, the size of the particles is related to the thickness of the coating. If the particle size is too large (such as >2.5μm), the coating will be too thick, which will cause the overall diaphragm to be too thick and affect the battery design space, ultimately reducing the battery capacity.
[0084] Furthermore, when the polyolefin emulsion is a polyethylene wax emulsion, the melting point of the solid particles is 60-160°C, preferably 80-135°C, more preferably 80-120°C, more preferably 110-120°C, and more preferably 80-90°C.
[0085] Here, the selection of the melting point of the solid particles is related to the closed-cell temperature. The upper limit should preferably be lower than the melting point of different polyolefin separators. For example, the upper limit is preferably 135°C. Therefore, when the polyolefin separator is UHMWPE, its melting point is around 135°C. At this time, the coating formed by the polymer emulsion with a melting point lower than 135°C can have a closed-cell temperature lower than that of the PE separator, thereby improving the overall safety performance of the battery. Other temperatures depend on different polyolefin materials and the preference when the closed-cell temperature of the separator is to be further reduced.
[0086] Further, the binder is selected from one or more of polyacrylates (such as polyacrylates and their derivatives), polyvinyl alcohols (such as polyvinyl alcohols and their derivatives), and polyvinyl acetate. Further, the dispersant is a water-soluble anionic surfactant or a cationic surfactant, preferably a combination of one or more of linear alkylbenzene sulfonate, sodium α-allyl sulfonate, sodium dodecyl sulfate, sodium fatty alcohol polyoxyethylene ether sulfate, coconut acid diethanolamide, sodium dodecylbenzene sulfonate, sodium ethoxylated alkyl sulfate, and dodecyl dimethyl betaine.
[0087] Furthermore, the organic solvent is an organic solvent that is miscible with deionized water in any proportion. The organic solvent is preferably selected from one or a mixture of two or more of ethanol, acetone, isopropanol, dimethylformamide, N,N-dimethylformamide, and dimethyl sulfoxide.
[0088] Furthermore, the substrate is a polyolefin membrane or a polyolefin membrane containing a ceramic coating.
[0089] Furthermore, the polyolefin in the polyolefin membrane or the polyolefin membrane containing a ceramic coating is one or a mixture of two or more of the following crystalline polymers: polyethylene, polypropylene, poly-1-butene, poly-4-methyl-1-pentene, poly-1-hexene, poly-1-octene or polymethyl methacrylate.
[0090] Furthermore, the ceramic particles in the ceramic coating include but are not limited to a mixture of one or more of aluminum oxide, boehmite, silicon oxide, magnesium hydroxide, zirconium oxide, tin oxide, calcium carbonate, barium titanate, barium sulfate, zinc oxide and titanium oxide.
[0091] Furthermore, the specific process of the ultraviolet irradiation is to use ultraviolet light with a wavelength range of 254 to 365 nm to irradiate the uncross-linked isolation film for 6 to 10 minutes, thereby obtaining the high temperature resistant coating film.
[0092] Here, the ultraviolet light with a wavelength range of 254 to 365 nm ensures both UV light penetration and absorption intensity, thereby improving the initiation efficiency, and the illumination time of 6 to 10 minutes can achieve the effect of uniform ultraviolet light irradiation. In the subsequent embodiments, as long as the process parameter range is adopted, there is no need to limit it, and different specific process parameter values will not bring different diaphragm performance.
[0093] Furthermore, in step 1), each component of the slurry is preferably a UV light initiator 0.1 ~ 2%, UV crosslinker 0.7 ~ 3.5%, deionized water 0 ~ 50%, polymer emulsion 0 ~ 83%, Binder 0 ~ 4.5%, dispersant 0 ~ 1.5%, organic solvent 8 ~ 58%.
[0094] When the slurry is mixed with a polymer emulsion, the components of the slurry in step 1) are further preferably 0.1 ~ 0.5%, UV crosslinker 0.7 ~ 0.9%, deionized water 0 ~ 19%, polymer emulsion 46 ~ 83%, Binder 0 ~ 4.1%, dispersant 0 ~ 1.2%, organic solvent 8 ~ 29%.
[0095] When the polymer emulsion in the slurry is a polyolefin emulsion, the components of the slurry in step 1) can be further preferably a UV initiator 0.3 ~ 0.5%, UV crosslinker 0.7 ~ 0.9%, deionized water 4 ~ 19%, polymer emulsion 47 ~ 81%, binder 3.5 ~ 4.1%, dispersant 0.9 ~ 1.2%, organic solvent 8 ~ 29%.
[0096] The high temperature resistant coating film prepared by the method provided in the specific embodiment of the present invention has a thickness of 9-18 μm, an air permeability of 144-230 s / 100 ml, a needle puncture strength of 472-616 gf, a closed cell temperature of 95-143° C., a film rupture temperature of 172-216° C., and a safety range of 35-91° C.
[0097] When the slurry is mixed with a polymer emulsion, the thickness is further preferably 9-18 μm, the air permeability is 176-230 s / 100 ml, the needle puncture strength is 473-509 gf, the closed-cell temperature is 95-141°C, the film rupture temperature is 172-216°C, and the safety range is 35-91°C.
[0098] When the polymer emulsion in the slurry is an emulsion of acrylic ester and its derivatives, it can be further preferably set to a thickness of 9 to 13 μm, an air permeability of 176 to 206 s / 100 ml, a needle puncture strength of 473 to 509 gf, a closed-cell temperature of 140 to 142°C, a film rupture temperature of 176 to 216°C, and a safety range of 35 to 75°C.
[0099] When the polymer emulsion in the slurry is a polyolefin emulsion, it can be further preferably set to a thickness of 9 to 18 μm, an air permeability of 152 to 230 s / 100 ml, a closed-cell temperature of 95 to 121° C., a film-breaking temperature of 172 to 187° C., and a safety interval of 50 to 91° C.
[0100] The specific embodiment of the present invention also provides a method for preparing a high temperature resistant coating film, comprising the following steps:
[0101] Weigh anhydrous ethanol, weigh the UV initiator and UV cross-linking agent, add them into the anhydrous ethanol, and shake them by ultrasonic until they are completely dissolved;
[0102] Deionized water is added to the ethanol solution containing the ultraviolet light initiator and the ultraviolet light co-crosslinking agent, and the mixture is stirred evenly to obtain a coating slurry.
[0103] The coating slurry is uniformly coated on one side or both sides of the substrate, and the high temperature resistant coating film is formed after being irradiated with ultraviolet light.
[0104] Here, the contents of the formulation components and the physical properties of the high temperature resistant coating film refer to the contents disclosed in the first specific embodiment.
[0105] The specific embodiment of the present invention also provides a method for preparing a high temperature resistant coating film, comprising the following steps:
[0106] Deionized water was weighed, and a water-soluble ultraviolet light initiator was weighed and completely dissolved in the deionized water to obtain a solution A.
[0107] Weigh anhydrous ethanol, add the ultraviolet light cross-linking agent into the ethanol, mix evenly until the ethanol is dissolved, and obtain solution B.
[0108] The solutions A and B were mixed and stirred at high speed to obtain a coating slurry.
[0109] The coating slurry is uniformly coated on one side or both sides of the substrate, and the high temperature resistant coating film is formed after being irradiated with ultraviolet light.
[0110] Here, the contents of the formulation components and the physical properties of the high temperature resistant coating film refer to the contents disclosed in the first specific embodiment.
[0111] The specific embodiment of the present invention also provides a method for preparing a high temperature resistant coating film, comprising the following steps:
[0112] Weigh anhydrous ethanol; weigh an ultraviolet light initiator and an ultraviolet light cross-linking agent, add them to the anhydrous ethanol, and perform ultrasonic vibration to completely dissolve them, thereby obtaining a solution A containing an ultraviolet light cross-linking agent and a cross-linking agent.
[0113] A is added into the emulsion of acrylate and its derivatives, and the mixed solution is stirred at high speed to obtain a coating slurry.
[0114] The coating slurry is uniformly coated on one side or both sides of the substrate, and the high temperature resistant coating film is formed after being irradiated with ultraviolet light.
[0115] Here, the contents of the formulation components and the physical properties of the high temperature resistant coating film refer to the contents disclosed in the first specific embodiment.
[0116] The specific embodiment of the present invention also provides a method for preparing a high temperature resistant coating film, comprising the following steps:
[0117] Deionized water is weighed, and a water-soluble ultraviolet photoinitiator is weighed and completely dissolved in the deionized water to obtain a solution A.
[0118] Weigh anhydrous ethanol, add the ultraviolet light cross-linking agent into the anhydrous ethanol and mix well to obtain solution B.
[0119] The two solutions A and B are stirred at high speed to be uniform, so as to obtain a mixed solution C containing an ultraviolet crosslinking agent and an auxiliary crosslinking agent.
[0120] Weigh the polyolefin emulsion, weigh the dispersant, weigh the acrylate adhesive, add the mixed solution C containing the ultraviolet crosslinking agent and the auxiliary crosslinking agent, the dispersant and the adhesive into the polyolefin emulsion, stir evenly at high speed to obtain a coating slurry.
[0121] The coating slurry is uniformly coated on one side or both sides of the substrate, and the high temperature resistant coating film is formed after being irradiated with ultraviolet light.
[0122] Here, the contents of the formulation components and the physical properties of the high temperature resistant coating film refer to the contents disclosed in the first specific embodiment.
[0123] The specific embodiment of the present invention also provides a method for preparing a high temperature resistant coating film, comprising the following steps:
[0124] Weigh anhydrous ethanol, add the UV initiator benzophenone and the UV co-crosslinking agent into the ethanol, stir and mix evenly at a high speed, after the UV crosslinking agent and the co-crosslinking agent are completely dissolved, add deionized water, stir and mix evenly to obtain a mixed solution A containing the UV crosslinking agent and the co-crosslinking agent.
[0125] Weigh the polyolefin emulsion, weigh the dispersant, weigh the binder, add the mixed solution A containing the ultraviolet crosslinking agent and the auxiliary crosslinking agent, the dispersant and the binder into the polyolefin emulsion, stir evenly at high speed to obtain a coating slurry.
[0126] The coating slurry is uniformly coated on one side or both sides of the substrate, and the high temperature resistant coating film is formed after being irradiated with ultraviolet light.
[0127] Here, the contents of the formulation components and the physical properties of the high temperature resistant coating film refer to the contents disclosed in the first specific embodiment.
[0128] The present invention will be described in detail below through examples.
[0129] In the following examples and comparative examples, the performance parameters were measured as follows:
[0130] 1. Thickness
[0131] The German Mahr film thickness gauge 1216 was used for testing with reference to the national standard GB / T 36363-2018 "Polyolefin separators for lithium-ion batteries".
[0132] 2. Air permeability
[0133] The test was carried out using Gurley air permeability tester 4110 with reference to the national standard GB / T 36363-2018 "Polyolefin separators for lithium-ion batteries".
[0134] 3. Acupuncture intensity
[0135] The test was carried out with reference to the national standard GB / T 36363-2018 "Polyolefin separators for lithium-ion batteries".
[0136] 4. Closed-cell temperature and film breaking temperature
[0137] The test was conducted in accordance with the patent "Testing Device for Batch Testing Thermal Closure Temperature and Film Breaking Temperature of Lithium Battery Diaphragms" (Publication No. CN211825790U). Cut a 15.8mm diaphragm sample, assemble it into a button battery after fully soaking it in the electrolyte, and gradually heat it to 250℃ for testing with a temperature accuracy of 0.01℃. Collect the internal resistance value of the diaphragm as it changes with temperature. According to the temperature at which the internal resistance suddenly changes, the diaphragm's closed-pore temperature and film breaking temperature are obtained.
[0138] Example 1
[0139] Weigh 50 parts by weight of anhydrous ethanol, weigh 0.4 parts by weight of ultraviolet light initiator benzophenone (BP) and 1.4 parts by weight of ultraviolet light co-crosslinking agent triallyl isocyanurate (TAIC), add them into the anhydrous ethanol and dissolve them completely, then add 50 parts by weight of deionized water and stir evenly.
[0140] A coating slurry 1 was obtained.
[0141] The coating slurry 1 was evenly coated on one side of the substrate of a 9-micron wet-process PE diaphragm, and the coated surface of the slurry 1 was cross-linked by ultraviolet radiation to obtain a high-temperature resistant diaphragm sample 1. The physical properties of sample 1 are shown in Table 1.
[0142] The coating slurry 1 was evenly coated on both sides of the substrate of a 9-micron wet-process PE diaphragm, and both sides coated with the slurry 1 were cross-linked by ultraviolet radiation to obtain a high-temperature resistant diaphragm sample 2. The physical properties of sample 2 are shown in Table 1.
[0143] The 9-micron wet-process PE diaphragm was used as blank sample 1 before coating. The comparative physical properties are shown in Table 1.
[0144] Example 2
[0145] 40 parts by weight of deionized water were weighed, and 1.6 parts by weight of a water-soluble ultraviolet light initiator 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone was weighed and completely dissolved in the deionized water to obtain a solution 2-A.
[0146] Weigh 60 parts by weight of anhydrous ethanol, add 3.4 parts by weight of ultraviolet light crosslinking agent triallyl isocyanurate (TAIC) into the ethanol, mix well and dissolve in the ethanol to obtain solution 2-B.
[0147] Mix slurries 2-A and 2-B and stir at high speed until uniform.
[0148] A coating slurry 2 was obtained.
[0149] The coating slurry 2 was evenly coated on one side of the substrate of a 12-micron wet-process PE diaphragm, and the coated surface of the slurry 2 was cross-linked by ultraviolet radiation to obtain a high-temperature resistant diaphragm sample 3. The physical properties of sample 3 are shown in Table 1.
[0150] The coating slurry 2 was evenly coated on both sides of the substrate of a 12-micron wet-process PE diaphragm, and the two sides coated with the slurry 2 were cross-linked by ultraviolet radiation to obtain a high-temperature resistant diaphragm sample 4. The physical properties of sample 4 are shown in Table 1.
[0151] Among them, the 12-micron wet-process PE diaphragm was used as blank sample 2 before coating, and the comparative physical properties are shown in Table 1.
[0152] Table 1 Comparison of physical properties before and after coating and crosslinking
[0153]
[0154] Example 3
[0155] Weigh 100 parts by weight of anhydrous ethanol; weigh 0.8 parts by weight of ultraviolet light initiator benzophenone (BP) and 4.2 parts by weight of ultraviolet light co-crosslinking agent trimethylolpropane trimethacrylate (TMPTMA), add them to the anhydrous ethanol, and perform ultrasonic vibration for 5 minutes to completely dissolve them, thereby obtaining a solution 3-A containing an ultraviolet light crosslinking agent and a co-crosslinking agent.
[0156] The obtained slurry 3-A is added into 480 parts by weight of acrylic ester copolymer emulsion, wherein the solid content of the acrylic ester copolymer emulsion is 33%, and the particle size D(50) of the solid particles is 0.6 μm.
[0157] Stir the mixed solution at high speed until uniform.
[0158] A coating slurry 3 was obtained.
[0159] The coating slurry 3 was evenly coated on one side of a 9-micron wet-process PE diaphragm substrate, and the coated side was cross-linked by ultraviolet irradiation to obtain a high-temperature resistant diaphragm sample 5. The physical properties of sample 5 are shown in Table 2.
[0160] The coating slurry 3 was evenly coated on both sides of the substrate of a 9-micron wet-process PE diaphragm, and the coated surface was cross-linked by ultraviolet irradiation to obtain a high-temperature resistant diaphragm sample 6. The physical properties of sample 6 are shown in Table 2.
[0161] The coating slurry 3 was evenly coated on the base film surface of the single-sided ceramic (9 micron base film + 3 micron ceramic coating) diaphragm, and the coated surface was cross-linked by ultraviolet irradiation to obtain a high temperature resistant diaphragm sample 7. The physical properties of sample 7 are shown in Table 2.
[0162] The coating slurry 3 was evenly coated on the ceramic coating surface of the single-sided ceramic (9 micron base film + 3 micron ceramic coating) diaphragm, and the coated surface was cross-linked by ultraviolet irradiation to obtain a high temperature resistant diaphragm sample 8. The physical properties of sample 8 are shown in Table 2.
[0163] The coating slurry 3 was evenly coated on the base film surface and the ceramic coating surface of the single-sided ceramic (9 micron base film + 3 micron ceramic coating) diaphragm, and the coated surface was cross-linked by ultraviolet irradiation to obtain a high temperature resistant diaphragm sample 9. The physical properties of sample 9 are shown in Table 2.
[0164] Among them, the 9-micron wet-process PE diaphragm was used as blank sample 1 before coating, and the comparative physical properties are shown in Table 1. The single-sided ceramic (9-micron base film + 3-micron ceramic coating) diaphragm was used as blank sample 3 before coating, and the physical properties after coating were compared, see Table 2 below.
[0165] Table 2 Comparison of physical properties before and after coating and crosslinking
[0166]
[0167] Example 4
[0168] Weigh 20 parts by weight of deionized water, weigh 1 part by weight of a water-soluble ultraviolet light initiator 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone and dissolve it completely in the deionized water to obtain a solution 4-A.
[0169] Weigh 30 parts by weight of anhydrous ethanol, add 3 parts by weight of ultraviolet light crosslinking agent trimethylolpropane trimethacrylate (TMPTMA) into the anhydrous ethanol and mix well to obtain solution 4-B.
[0170] The two solutions 4-A and 4-B were stirred at high speed to obtain
[0171] Mixed solution of UV crosslinking agent and auxiliary crosslinking agent 4~C.
[0172] Weigh 266 parts by weight of a polyolefin wax emulsion, wherein the solid polyolefin particles in the polyolefin emulsion have a melting point between 110 and 120° C., the particle size D(50) of the polyolefin particles is 1.5 μm, and the solid content of the solid polyolefin particles in the polyolefin emulsion is 42%.
[0173] Weigh 3 parts by weight of the dispersant dodecyl dimethyl betaine.
[0174] Weigh 12 parts by weight of an acrylic adhesive.
[0175] Add a mixed solution 4-C containing an ultraviolet crosslinking agent and an auxiliary crosslinking agent, a dispersant dodecyl dimethyl betaine and an acrylate adhesive into the polyolefin wax emulsion and stir at a high speed to make it uniform.
[0176] A coating slurry 4 was obtained.
[0177] The coating slurry 4 was evenly coated on one side of a 9-micron wet-process PE diaphragm substrate, and the coated side was cross-linked by ultraviolet radiation to obtain a high-temperature resistant diaphragm sample 10. The physical properties of sample 10 are shown in Table 3.
[0178] The coating slurry 4 was evenly coated on both sides of the substrate of a 9-micron wet-process PE diaphragm, and the coated side was cross-linked by ultraviolet irradiation to obtain a high-temperature resistant diaphragm sample 11. The physical properties of sample 11 are shown in Table 3.
[0179] The coating slurry 4 was evenly coated on the base film surface of the single-sided ceramic (9 micron base film + 3 micron ceramic coating) diaphragm, and the coated surface was cross-linked by ultraviolet irradiation to obtain a high temperature resistant diaphragm sample 12. The physical properties of sample 12 are shown in Table 3.
[0180] The coating slurry 4 was evenly coated on the ceramic surface of the single-sided ceramic (9 micron base film + 3 micron ceramic coating) diaphragm, and the coated surface was cross-linked by ultraviolet irradiation to obtain a high temperature resistant diaphragm sample 13. The physical properties of sample 13 are shown in Table 3.
[0181] The coating slurry 4 was evenly coated on both sides of the single-sided ceramic (9 micron base film + 3 micron ceramic coating) diaphragm, and the coated surface was cross-linked by ultraviolet irradiation to obtain a high temperature resistant diaphragm sample 14. The physical properties of sample 14 are shown in Table 3.
[0182] Among them, the 9-micron wet-process PE diaphragm was used as blank sample 1 before coating, and the comparative physical properties are shown in Table 1. The single-sided ceramic (9-micron base film + 3-micron ceramic coating) diaphragm was used as blank sample 3 before coating, and the physical properties were compared with those after coating, as shown in Table 3 below.
[0183] Table 3 Comparison of physical properties before and after coating and crosslinking
[0184]
[0185] Example 5
[0186] Weigh 35 parts by weight of anhydrous ethanol, add 1.5 parts by weight of UV initiator benzophenone and 3 parts by weight of UV co-crosslinker trimethylolpropane trimethacrylate (TMPTMA) into the ethanol and stir at high speed to mix evenly. After the UV crosslinker and co-crosslinker are completely dissolved, add 15 parts by weight of deionized water and stir evenly. A mixed solution containing UV crosslinker and co-crosslinker is obtained.
[0187] Weigh 300 parts by weight of an aqueous polyolefin wax emulsion, wherein the solid polyolefin particles in the polyolefin emulsion have a melting point between 80 and 90° C., a particle size D(50) of the polyolefin particles is 1.0 μm, and a solid content of the solid polyolefin particles in the polyolefin emulsion is 35%.
[0188] Weigh 3.5 parts by weight of the dispersant sodium linear alkylbenzene sulfonate.
[0189] Weigh 15 parts by weight of an acrylic adhesive.
[0190] Add the mixed solution 5-A containing the ultraviolet crosslinking agent and the auxiliary crosslinking agent, the dispersant linear alkylbenzene sodium sulfonate and the acrylic ester binder into the polyolefin wax emulsion and stir at high speed to make it uniform.
[0191] A coating slurry 5 was obtained.
[0192] The coating slurry 5 was evenly coated on one side of a 12 μm wet-process PE diaphragm substrate, and the coated side was cross-linked by ultraviolet radiation to obtain a high temperature resistant diaphragm sample 15. The physical properties of sample 15 are shown in Table 4.
[0193] The coating slurry 5 was evenly coated on both sides of the substrate of a 12 μm wet-process PE diaphragm, and the coated surface was cross-linked by ultraviolet radiation to obtain a high-temperature resistant diaphragm sample 16. The physical properties of sample 16 are shown in Table 4.
[0194] Among them, the 12-micron wet-process PE diaphragm was used as blank sample 2 before coating, and the comparative physical properties are shown in Table 4.
[0195] Table 4 Comparison of physical properties before and after coating and crosslinking
[0196]
[0197] Example 6
[0198] Weigh 60 parts by weight of anhydrous ethanol, weigh 1 part by weight of ultraviolet light initiator benzophenone (BP) and 1.5 parts by weight of ultraviolet light co-crosslinking agent triallyl isocyanurate (TAIC), add them into the anhydrous ethanol and dissolve them completely. Then add 40 parts by weight of deionized water, stir and mix them evenly, and obtain a mixed solution 6-A containing an ultraviolet light crosslinking agent and a co-crosslinking agent.
[0199] Weigh 100 parts by weight of an aqueous polyolefin wax emulsion, wherein the solid polyolefin particles in the polyolefin emulsion have a melting point between 110 and 120° C., the particle size D(50) of the polyolefin particles is 1.2 μm, and the solid content of the solid polyolefin particles in the polyolefin emulsion is 65%.
[0200] Weigh 2.5 parts by weight of the dispersant sodium linear alkylbenzene sulfonate.
[0201] Weigh 8 parts by weight of an acrylic adhesive.
[0202] Add the mixed solution 6-A containing the ultraviolet crosslinking agent and the auxiliary crosslinking agent, the dispersant linear alkylbenzene sodium sulfonate and the acrylic ester binder into the polyolefin wax emulsion and stir at high speed to make it uniform.
[0203] A coating slurry 6 was obtained.
[0204] The coating slurry 6 was evenly coated on one side of a 12 μm wet-process PE diaphragm substrate, and the coated side was cross-linked by ultraviolet irradiation to obtain a high temperature resistant diaphragm sample 17. The physical properties of sample 17 are shown in Table 4.
[0205] The coating slurry 6 was evenly coated on both sides of the substrate of a 12 μm wet-process PE diaphragm, and the coated surface was cross-linked by ultraviolet radiation to obtain a high-temperature resistant diaphragm sample 18. The physical properties of sample 18 are shown in Table 4.
[0206] Among them, the 12-micron wet-process PE diaphragm was used as blank sample 2 before coating, and the comparative physical properties are shown in Table 5.
[0207] Table 5 Comparison of physical properties before and after coating and crosslinking
[0208]
[0209]
[0210] The above contents involving common knowledge are not described in detail, and those skilled in the art can understand them.
[0211] The above descriptions are only some specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention shall be included in the protection scope of the present invention. The technical scope of the present invention is not limited to the contents of the specification, but must be determined according to the scope of the claims.
Claims
1. A high temperature resistant coating film, characterized in that: The safety range of the high temperature resistant coating film is 35 to 91°C.
2. The high temperature resistant coating film according to claim 1, characterized in that: The closed-cell temperature of the high-temperature resistant coating film is 95-143°C, and the film-breaking temperature of the high-temperature resistant coating film is 172-216°C.
3. The high temperature resistant coating film according to claim 2, characterized in that: The thickness of the high temperature resistant coating film is 9-18 μm, the air permeability of the high temperature resistant coating film is 144-230 s / 100 ml, and the needle puncture strength of the high temperature resistant coating film is 472-616 gf.
4. The high temperature resistant coating film according to claim 1, characterized in that: The high temperature resistant coating film comprises a substrate and a coating slurry on at least one surface of the substrate; the coating slurry comprises the following components in percentage by mass: 0.01-5% of ultraviolet initiator, 0.01-5% of ultraviolet crosslinker, 0-50% of deionized water, and 5-70% of organic solvent.
5. The high temperature resistant coating film according to claim 1, characterized in that: The high temperature resistant coating film comprises a substrate and a coating slurry on at least one surface of the substrate; the coating slurry comprises the following components in percentage by mass: 0.01-5% ultraviolet initiator, 0.01-5% ultraviolet crosslinker, 0-90% polymer emulsion, and 5-70% organic solvent.
6. The high temperature resistant coating film according to claim 1, characterized in that: The high temperature resistant coating film comprises a substrate and a coating slurry on at least one surface of the substrate; the coating slurry comprises the following components in percentage by mass: 0.01-5% of ultraviolet initiator, 0.01-5% of ultraviolet crosslinker, 0-50% of deionized water, 0-90% of polymer emulsion, 0-10% of binder, 0-5% of dispersant, and 5-70% of organic solvent.
7. The high temperature resistant coating film according to any one of claims 4 to 6, characterized in that: The organic solvent is an organic solvent that is miscible with water in any proportion.
8. The high temperature resistant coating film according to any one of claims 4 to 6, characterized in that: The ultraviolet light initiator is a cationic light initiator or a free radical light initiator.
9. The high temperature resistant coating film according to any one of claims 4 to 6, characterized in that: The ultraviolet crosslinking agent is an allyl auxiliary crosslinking agent.
10. The high temperature resistant coating film according to claim 5 or 6, characterized in that: The polymer emulsion is polyolefin emulsion, acrylate and its derivative emulsion.
11. The high temperature resistant coating film according to claim 6, characterized in that: The binder is selected from one or more of polyacrylate and its derivatives, polyvinyl alcohol and its derivatives, and polyvinyl acetate.
12. The high temperature resistant coating film according to claim 6, characterized in that: The dispersant is an anionic surfactant or a cationic surfactant.
13. The high temperature resistant coating film according to claim 4, characterized in that: The ultraviolet light initiator is benzophenone, the ultraviolet light crosslinking agent is triallyl isocyanurate, and the organic solvent is anhydrous ethanol.
14. The high temperature resistant coating film according to claim 4, characterized in that: The ultraviolet light initiator is 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, the ultraviolet light crosslinking agent is triallyl isocyanurate, and the organic solvent is anhydrous ethanol.
15. The high temperature resistant coating film according to claim 5, characterized in that: The ultraviolet light initiator is benzophenone, the ultraviolet light crosslinking agent is trimethylolpropane trimethacrylate, the polymer emulsion is an acrylate and its derivative emulsion, and the organic solvent is anhydrous ethanol.
16. The high temperature resistant coating film according to claim 6, characterized in that: The ultraviolet light initiator is 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, the ultraviolet light crosslinking agent is trimethylolpropane trimethacrylate, and the dispersant is dodecyl dimethyl betaine.
17. The high temperature resistant coating film according to claim 6, characterized in that: The ultraviolet light initiator is benzophenone, the ultraviolet light crosslinking agent is trimethylolpropane trimethacrylate, and the dispersant is linear sodium alkylbenzene sulfonate.
18. The high temperature resistant coating film according to claim 6, characterized in that: The ultraviolet light initiator is benzophenone, the ultraviolet light crosslinking agent is triallyl isocyanurate, and the dispersant is sodium linear alkylbenzene sulfonate.
Citation Information
Patent Citations
Non-woven ceramic membrane with excellent closed-pore performance for lithium ion battery and technology
CN103199209A
A coating slurry for diaphragms, a composite heat-resistant diaphragm, and a method for preparing the same.
CN106252570B
Testing device for testing thermal hole closing temperature and membrane breaking temperature of lithium battery diaphragms in batches
CN211825790U